Green Shoots:: Aerial Insecticide Spraying and the Growth of Environmental Consciousness in New Brunswick, 1952-1973 - McLaughlin, Mark (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2011)
Abstract Modern environmentalism in New Brunswick was triggered primarily by the growth of opposition to New Brunswick’s controversial spruce budworm spraying program in the 1950s and 1960s. While this "Battle of the Budworm" initially arose from concern within sportsmen’s organizations over the effects of the DDT spray on Atlantic salmon, research by the province’s scientific and technical community fostered greater opposition to the spraying – opposition that challenged the provincial government’s traditional stance on resource management. Forest industry and provincial government officials countered assertions of massive ecological damage by arguing that the spraying program was necessary to save the province’s forests and forest industries.